Gender and age differences in emotional management among elite taekwondo coaches - Abello, G. A. S.; Viviescas, A. M. A.; Saca, P. S. O.; Treuque, F. A. R. (Scientific Journal of Sport and Performance, 2025)
Emotional management is a psychological aspect that has been widely researched in the sports context; however, most of these studies have focused on evaluating athletes, overlooking other key figures such as coaches. To identify gender and age differences in the emotional management of elite taekwondo coaches. This is a quantitative, descriptive study with a non-experimental design to describe and identify differences within a sample of 20 elite taekwondo coaches. Emotional intelligence was assessed using the Schutte Self-Report Emotional Intelligence Test (SSEIT). Welch's t-test and ANOVA were conducted to determine differences by gender and age groups among the coaches. Significant differences were found in emotional intelligence between men and women (p < .065) and in emotion perception, where women scored higher than men (p < .012). No significant differences were found between men and women in self-emotion management, managing others' emotions, and emotion utilization. Regarding age groups, no significant differences were observed in emotional intelligence, emotion perception, self-emotion management, and emotion utilization. However, a marginally significant difference was found in managing others' emotions (p < .051), suggesting a possible age influence on this variable. The study revealed that female taekwondo coaches have significantly higher emotional intelligence and emotion perception than their male counterparts. No significant differences were found in other areas of emotional management between genders. However, a positive influence of age on managing others' emotions was observed. These findings highlight the importance of considering gender and age in the training of taekwondo coaches and the need for further research in these areas.